2019
DOI: 10.3354/esr00936
|View full text |Cite
|
Sign up to set email alerts
|

First estimates of entanglement rate of humpback whales Megaptera novaeangliae observed in coastal Icelandic waters

Abstract: hundreds of thousands of individuals (Read et al. 2006). Most types of fishing gear (e.g. gillnets, long lines, and pot/trap lines) are known to cause entanglements (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…A sighting in June of that year revealed that Spinnaker had unhealed injuries from a recent, unreported entanglement, but the injuries were similar in nature and severity to those routinely documented among free-swimming whales in this population (e.g. Robbins and Mattila, 2001 ; Robbins, 2012 ) and others ( Neilson et al , 2009 ; Basran et al, 2019 ; Ramp et al, 2021 ). Although her corticosterone levels were still much higher than the other whales, her average cortisol (1.505 ng/g) was comparable to SEAK 68 (1.844 ng/g, ship strike death) and SEAK 441 (1.618 ng/g, chronic illness; Fig.…”
Section: Resultsmentioning
confidence: 79%
“…A sighting in June of that year revealed that Spinnaker had unhealed injuries from a recent, unreported entanglement, but the injuries were similar in nature and severity to those routinely documented among free-swimming whales in this population (e.g. Robbins and Mattila, 2001 ; Robbins, 2012 ) and others ( Neilson et al , 2009 ; Basran et al, 2019 ; Ramp et al, 2021 ). Although her corticosterone levels were still much higher than the other whales, her average cortisol (1.505 ng/g) was comparable to SEAK 68 (1.844 ng/g, ship strike death) and SEAK 441 (1.618 ng/g, chronic illness; Fig.…”
Section: Resultsmentioning
confidence: 79%
“…This is particularly true for pot/trap and gillnet gears which are left in the water, unattended, for longer periods of time and are well known for entangling whales (Johnson et al, 2005). For example, in Iceland, a study based on scarring estimated that a minimum of 25% of humpback whales have been entangled previously (Basran et al, 2019) and additionally 15% of questionnaire respondents witnessed humpback whales interact with their fishing gear (Basran and Rasmussen, 2021). Furthermore, there have been reports of humpback whale deaths due to entanglement in interviews with fishing vessel captains (Basran and Rasmussen, 2021), and based on examination of stranded animals (Víkingsson et al, , 2005Víkingsson, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between whales and gear also causes financial loss to fisheries in terms of gear damage, down-time for repairs and loss of catch (Lien, 1979;Lien and Aldrich, 1982), particularly large whale interactions such as humpback whales. For humpback whales, it is estimated that the studied populations in Iceland, the Gulf of Maine, and Alaska are entangled in fishing gear at a rate of 2%, 14-17% and 8% per year respectively (Basran et al, 2019;Robbins, 2012;Neilson et al, 2009). Possibly due to the concern over negative consequences for the fishing industry, under-reporting of bycatch and interactions with large marine mammals is common (e.g.…”
Section: Introductionmentioning
confidence: 99%